Student-Designed Cross-Sectional Pandemic Knowledge Survey of 8th−12th Grade Students, Milwaukee, WI, April 2020 - Vasudev, Krish; Singh, Hersh; Neumann, August A.; Zhao, William M; Mondano, Lyle Dominic Pelayo (Frontiers in Pediatrics, 2021)
BACKGROUND: The novel coronavirus and its effect on our society are unprecedented. Given the recent pandemic, numerous measures have been taken to protect our communities. We sought to understand our school community’s knowledge and the measures that were taken by our school for our safety. OBJECTIVE: Our objective was to describe the overall understanding and attitudes of 8-12th grade students from a single institution during the initial phase of the Wisconsin’s Governor’s stay-at-home order. METHODS: A voluntary web-based survey was communicated to 8-12th grade students through their online school portal. Data was collected and analyzed using SurveyMonkey. RESULTS: There was a 20.2% response rate. Answers regarding the coronavirus, spread, and response to the coronavirus pandemic showed a high level of understanding of the virus and the actions necessary to prevent its spread. CONCLUSION: 8-12th grade students have a high level of understanding of the virus, its effects, and the safety measures implemented to protect society.